Pharmacological characterization and preclinical evaluation of 11h: a novel, brain-penetrant PDE4 inhibitor for neurological disorders - Lackovic, Jacob; Dey, Sougata; Ward, Sara Jane; Greig, Nigel H.; Tweedie, David; Beiranvand, Nassim; Saini, Uksha; Chatterjee, Dev; Varadhachary, Atul (Frontiers in Pharmacology, 2026)
BackgroundPhosphodiesterase 4 (PDE4) inhibitors hold promise for treating neuroinflammatory and neurodegenerative disorders, but their clinical application in central nervous system (CNS) diseases has been limited by insufficient brain penetration and adverse effects, especially nausea and vomiting. In this study, we characterize compound 11h, a novel, orally available, brain-penetrant PDE4 inhibitor designed to address these limitations.Methods11h was evaluated using integrated computational, in vitro, and in vivo approaches, including Schrödinger-based molecular docking against human PDE4A10, luminescence-based cAMP assays for PDE4 isoform inhibition, and inflammatory assays in murine macrophages, microglia-like cells, and human PBMCs. In vivo efficacy, pharmacokinetics, brain and tissue distribution, tolerability, emesis liability, and behavioral effects were assessed across mouse, rat, and ferret models, alongside comprehensive safety pharmacology encompassing CYP450 inhibition, cardiac ion channel profiling, mutagenicity, and off-target screening.Results11h demonstrated potent, broad-spectrum inhibition across all four PDE4 isoforms, including key PDE4D splice variants (PDE4D2, PDE4D3), with low nanomolar IC50 values. In vitro, 11h significantly reduced the release of tumor necrosis factor alpha (TNFα), interleukin 6 (IL-6), and nitrites in lipopolysaccharide (LPS)-stimulated macrophages, microglia-like cells, and human peripheral blood mononuclear cells without affecting cell viability. In vivo, 11h attenuated neuroinflammation in LPS-treated mice by decreasing M1 macrophages and CD4+ T cells, increasing M2 macrophages, and downregulating pro-inflammatory cytokines and MyD88 pathway genes. Pharmacokinetic analysis in rats confirmed strong oral bioavailability, dose-proportional systemic exposure, and sustained brain concentrations exceeding plasma levels for up to 48 h post-dose. Importantly, 11h did not induce vomiting in the ferret emesis model even at doses exceeding 50-fold the efficacious levels in rodent disease models, and was well tolerated in behavioral assays, where it produced anxiolytic-and antidepressant-like effects. Safety profiling revealed no cytotoxicity, genotoxicity, or significant inhibition of cardiac ion channels or cytochrome P450 enzymes. Consistent with this experimental profile, molecular docking suggested that 11h preferentially engages a pocket within the PDE4 catalytic domain, with high predicted binding affinity and ligand efficiency driven by hydrophobic and electrostatic interactions.ConclusionThese findings suggest that 11h provides broad PDE4 inhibition with a favorable tolerability and pharmacokinetic profile relative to approved PDE4 inhibitors, supporting its further development as a therapeutic candidate for CNS disorders characterized by neuroinflammation.